Prophetic Tax Based on Kuntowijoyo's Thought - Umaimah; Triyuwono, Iwan; Purwanti, Lilik (Accounting Department,, 2024)
Purpose —. This research aims to formulate a tax concept based on Kuntowijo's thought. Design/methodology/approach —. This research is critical research using Kuntowijoyo's critical thinking, namely the prophetic mission of Islam; humanization, liberation, and transcendence based on Al Quran Surah Ali Imron verse 110 Findings — Humanization, liberation and transcendence do not yet exist in the modern tax concept. Taxes should be a sincere gift from the people to the State based on justice within the framework of faith in God Almighty and spent on the interests of the people from the weakest groups. Practical implications — It is hoped that this article can be used as material for consideration for the government, especially the Directorate General of Taxes, to reformulate the concept of tax in Indonesia. Originality/value — This article presents a tax concept that combines Religion with human thought.